A photo-narrative intervention protocol for clinicians and parents of children with severe neurological impairment in the PICU - Jori Bogetz; Elsa Ayala; Jordan Anderson; Liz Morris; Krysta S. Barton; Miranda C. Bradford; Chuan Zhou; Joyce Yi-Frazier; R. Scott Watson; Abby R. Rosenberg (Contemporary Clinical Trials Communications)
Background: Children with severe neurological impairment (SNI) have central nervous system conditions that result in medical complexity and lifelong caregiver assistance. When children with SNI are admitted to the pediatric intensive care unit (PICU), their parents/families may experience elevated stress due to poor communication with clinicians. Methods: To address this, we created a photo-narrative intervention designed to facilitate parent-clinician communication. The intervention asks parents/families to share 3 photos with captions that inform clinicians about their child's well-being and quality-of-life. The steps include: 1) learning about photo-narratives; 2) deciding on a story; 3) selecting photos; and 4) identifying the broader context. Clinicians receive a companion guide on how to use the photo-narrative. In this pilot randomized controlled trial, N = 40 parent/family caregivers of children with SNI and their child's PICU clinicians will be randomized to receive the photo-narrative intervention or usual care. Participants will complete study surveys at enrollment and the child's PICU discharge; intervention-arm participants will also complete semi-structured interviews at discharge. The primary aim is to describe: 1) feasibility, assessed by the recruitment (approached/enrolled) and completion (intervention completion/intervention-arm) rates; and 2) acceptability (recommend the intervention/intervention-arm). We also will evaluate proof of concept by comparing changes in parent self-reported stress, perceptions of therapeutic alliance, and effects on stigma, resilience, benefit-finding, and respect as well as clinician self-reported empathy and perspective-taking. Discussion: This study will evaluate the feasibility and acceptability of a novel photo-narrative intervention designed to improve caregiver stress and communication. Findings will guide the development of future multisite studies. Clinical trial registration: NCT06208332.